The Pathway Relationship Between Physical Activity Levels and Depressive Symptoms in University Students Mediated by Cognitive Flexibility - Fen Yu; Shuqi Jia; Qin Liu; Zhaohui Guo; Sen Li; Xing Wang; Pan Li (Brain and Behavior)
ABSTRACT Objective To explore the mediating pathway of cognitive flexibility in the relationship between physical activity and depressive symptoms among university students. Methods A cross‐sectional design was used to survey 2537 university students using the Physical Activity Rating Scale‐3, Patients’ Health Questionnaire, and Cognitive Flexibility Inventory. Data analysis was conducted using independent samples t‐test, chi‐square test, correlation analysis, one‐way ANOVA, and mediation analysis. Results A statistically significant negative correlation exists between the intensity of physical activity and depression symptom scores (r = −0.104, p < 0.01). The intensity of physical activity demonstrates a statistically significant positive correlation with controllability (r = 0.109, p < 0.01). A marked negative correlation is observed between depressive symptoms and controllability scores (r = −0.367, p < 0.01). The total effect of physical activity intensity on depressive symptoms was quantified as −0.3542 (95% CI: −0.5439 to −0.1645). The direct effect was found to be ‐0.2199 (95% CI: ‐0.3981, ‐0.0417), while the mediating effect of controllability was calculated to be −0.1343 (95% CI: −0.2145 to −0.0630). Conclusion Increased engagement in physical activity among university students is associated with a reduction in their depressive symptom scores. Controllability serves as a mediating factor in the relationship between physical activity and depressive symptoms among university students.